FINANCIAL INCLUSION AS A PARADOX FOR ECONOMIC GROWTH IN NIGERIA - Majeed Ajibola IBRAHIM; Olawale DADA; Kayode Abdul-Ganiyu AKANBI; Lateef Kayode JAJI (Malete Journal of Accounting and Finance)
Access to financial services at affordable rate is one of the major concerns of financial inclusion in both advanced and developing nation around the globe since the subject matter is considered as a key driver for economic growth acceleration. This paper sought to empirically examine how financial inclusion variables (financial deepening, access to finance, saving mobilization and liquidity ratio) contribute to economic growth in Nigeria (2008-2022). Data for the study were collected secondarily from Statistical Bulletins of the Central Bank of Nigeria (C.B.N.) and Federal Office of Statistics (F.O.S.). Specifically, data consisting of economy and bank parametric which include GDP, financial deepening represented by (FD1 and FD2), Total loan and advances of the deposit money banks (LA), Total Deposit of the deposit money banks (TD) and Liquidity ratio (LQR) of deposit money banks spanning about twenty five-year period; 2008 to 2022 were extracted. OLS regression analysis was adopted, and the entire outcomes of the regression analysis indicates a positive relationship exist between the financial inclusion and economic growth in Nigeria given cognizance to the reported coefficients on each of the adopted variables. Therefore, it was recommended that financial regulators should request for comprehensive and adequate policy guidance that will encourage financial inter-mediation across board as this will no doubt foster economy growth.